Does fluoride cause DNA damage? An 'in vitro' evaluation using rats oral mucosa cells - Daniel Araki Ribeiro; Daisy Maria Fávero Salvadori; Gerson Francisco Assis; Mariângela Esther Alencar Marques (Universidade Estadual de Campinas, 2015)
Due to its properties, fluoride (NaF) is widely used in dentistry, as a tool for dental caries control and prevention; nevertheless, the inadequate use of fluoride may cause odontogenesis disturbance and citotoxicity on soft tissues. So that, this report proposed to evaluate the genotoxic effects of NaF under following concentrations: 0, 7, 28, 56 and 100 ppm, on rats' oral cells in vitro, through the comet assay. The results showed that NaF, in different concentrations analyzed, it did not promote genotoxic alterations on both keratinocytes, with and without lysis of the cytoplasm. Based on the results, it concluded that NaF, in these concentrations tested, it did not cause genotoxic alterations on rats' oral cells and the comet assay on oral mucosa may be helpful to evaluate the genotoxic potential of some substances usually in contact with oral mucosa as fluoride.